Kryptonesticus deelemanae gen. et sp. nov. (Araneae, Nesticidae), with notes on the Mediterranean cave species - Pavlek, Martina; Ribera, Carles (European Journal of Taxonomy, 2017)
This paper describes and illustrates a new genus and a new species belonging to the family Nesticidae based on morphology and supported by molecular data. The new genus, Kryptonesticus gen. nov., groups eight species spread from Bulgaria and Turkey to Croatia, including Montenegro, Bosnia and Herzegovina and Crete. As a result, seven new combinations are proposed: K. eremita (Simon, 1879) comb. nov., K. arenstorffi (Kulczyński, 1914) comb. nov., K. fagei (Kratochvíl, 1933) comb. nov., K. beroni (Deltshev, 1977) comb. nov., K. beshkovi (Deltshev, 1979) comb. nov., K. henderickxi (Bosselaers, 1998) comb. nov. and K. dimensis (López-Pancorbo, Kunt & Ribera, 2013) comb. nov., all ex Nesticus. Kryptonesticus deelemanae gen. et sp. nov. is described on the basis of both sexes and its phylogenetic relationships with closely related species are discussed based on morphological and molecular data (the cox1, rrn and H3 genes). In addition, the species of this new genus (except for K. eremita) are clear candidates for protection: they have highly restricted ranges and some of them show a high degree of adaptation to the subterranean environment.